COUNTER TERRORISM AND HUMAN RIGHTS VIOLATION IN THE AFTERMATH OF TERRORISM IN INDONESIA - Heru Susetyo (Hukum Pidana dan Pembangunan Hukum, 2018)
In the aftermath of Bali Bombing 12 October 2002, which is considered as the biggest terrorism attack ever in Indonesia,   the Indonesian government launched so called ‘war against terrorism’.  Laws on terrorism were soon enacted and applied retroactively.   Special Police to Combat Terrorism, namely Detachment of 88 was formed.  Special Agency to coordinate counterterrorism measures was soon established, namely Badan Nasional PenanggulanganTerorisme or National Agency for Terrorism Countermeasures.  Since early 2010’s it has conducted special program to combat terrorism namely deradicalization program while the Detachment of 88 has launched more massive manhunt for suspected terrorism all over Indonesia,  supported by Indonesian military.  Deradicalization program targets former terrorism suspects and former inmates.  Also, it targets schools, universities, and other academic institutions suspected as being an agent for radical ideology dissemination in Indonesia.  Both deradicalization program and massive manhunt have created problems.  At one side the Agency claimed that they have prevented terrorism, but on the other hand, they have victimized innocent people such as family of terrorist suspects and violated civil rights of former inmates.  In addition, by targeting specific academic institutions, the agency has been accused as arbitrarily labeling people as terrorist or future terrorist, which is a clear violation of human rights. This research, therefore, is a study of counter-terrorism, including deradicalization program in Indonesia. It tries to describe the dynamic of the program between the need of law enforcement in the name of law enforcement and its impact to human rights and civil liberty.  Keywords:  Deradicalization, Terrorism, Victimization, Indonesia, Human Rights